2017
DOI: 10.1158/1541-7786.mcr-16-0085-t
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Localized LSR: A Novel Regulator of Breast Cancer Behavior and Tumorigenesis

Abstract: Lipolysis Stimulated Lipoprotein Receptor (LSR) has been found in the plasma membrane and is believed to function in lipoprotein endocytosis and tight junctions. Given the impact of cellular metabolism and junction signaling pathways on tumor phenotypes and patient outcome, it is important to understand how LSR cellular localization mediates its functions. We conducted localization studies, evaluated DNA binding, and examined the effects of nuclear LSR in cells, xenografts, and clinical specimens. We found LSR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 62 publications
0
24
0
Order By: Relevance
“…However, the inhibitory effect of anti-hLSR mAb (#1-25) in vitro was not as intense as its effect in vivo. In breast cancer, a relationship between angiogenesis and nuclear-localized LSR has been reported (38). We targeted and analyzed membrane-localized LSR; however, downstream effects of LSR might involve angiogenesis, and our anti-LSR mAb (#1-25) might also inhibit this process in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…However, the inhibitory effect of anti-hLSR mAb (#1-25) in vitro was not as intense as its effect in vivo. In breast cancer, a relationship between angiogenesis and nuclear-localized LSR has been reported (38). We targeted and analyzed membrane-localized LSR; however, downstream effects of LSR might involve angiogenesis, and our anti-LSR mAb (#1-25) might also inhibit this process in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have not made a connection between the Daxx nuclear/cytoplasmic expression ratio and GC, and this is the first study of its type to use Daxx IHC in clinical gastric carcinoma tissue. Numerous previous studies have shown that protein subcellular localization can be closely related to tumor progression. In this study, we found that the subcellular localization of Daxx in cells is complex, because it is expressed in both the nucleus and the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that a protein's subcellular locations may be associated with different functions. In fact, numerous studies have shown that protein subcellular localization can be associated with functions that are closely related to tumor progression .…”
Section: Introductionmentioning
confidence: 99%
“…The progression of normal epithelial cells to CRC involves multiple gene mutations within several signaling pathways, such as the Wnt signaling pathway, MAPK signaling pathway, PI3K signaling pathway, TGFβ signaling pathway, and p53 signaling pathway [11]. While APC, CTNNB1, LSR, TOPORS, KLF5, IGF1 and SOX9 are related to Wnt signaling pathways, KRAS and BRAF are involved in RAS signaling pathways [54,55,56,57,58,59,60]. This indicates that the abnormalities of proliferative pathways may crucial in early colorectal cancer development.…”
Section: Discussionmentioning
confidence: 99%